Pengaruh Tingkat Literasi Kebencanaan Siswa SMA Muhammadiyah 1 Sragen Terhadap Pengetahuan Kebencanaan Di Kabupaten Sragen - Nurhalimah, Devi; Zarka, Aqila Ummu; Wardhani, Puspita Indra (Universitas Pendidikan Ganesha, 2024)
The disaster risk index in Sragen Regency had a moderate threat class that could increase the potential for disaster. This required disaster-related knowledge that could be obtained through disaster literacy activities. This study aimed to determine the effect of the level of disaster literacy of Muhammadiyah 1 Sragen High School students on disaster knowledge in Sragen Regency. The research method used was quantitative research with a correlation design obtained using a questionnaire specifically designed for data collection. The results of this study indicate that the level of disaster literacy of Muhammadiyah 1 Sragen High School students is categorized as high with an average score of 62%. Second, the level of students' disaster knowledge is categorized as moderate, with an average score of 70%. Statistical tests show that there is a strong relationship between disaster literacy and students' disaster knowledge with a significant value of 0.579. Based on data analysis, the conclusion is that disaster literacy plays a part in increasing disaster-related knowledge to reduce disaster risk.